(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial Intelligence (AI) and Sensor Technologies making a point-of-care delivery possible which was considered impossible. The human body shows early indicators of disease manifestation before actual clinical symptoms appear. These indicators can be picked up by analyzing the optical face image, which can be used for rapid and cost-effective screening of life-threatening health conditions. This article focuses on how health status can be tracked using optical image analytics. Early identification of disease plays a vital role in therapeutics of a patient. In accordance with review of secondary data available in literature, this article proposed a model to rapidly screen the health conditions at point-of-care. The patterns in the optical image have the potential to act as digital disease markers.